Retaining Front-Line Personnel in a Pandemic: Examining the Effects of Preparation and Capacity to Respond - Henderson, Alexander C.; Melitski, James (International journal of public administration, 2024)
The COVID-19 pandemic has placed significant stress on public services, including front-line personnel in a variety of core government positions like policing. Past research in law enforcement has long described challenges related to these ideas of uncertainty, stress, and situational difficulties, and the effects of those on individual and group behavior and work practices. This exploratory research focuses on the retention of these key personnel in the midst of a pandemic. Survey data were collected in 2020 and 2021 from law enforcement personnel at all departmental ranks. Results indicate that there is wide variation in feelings of preparedness and efficacy of response, and that those with stronger perceptions of organizational capacity to respond to the pandemic, increased job satisfaction, and higher organizational commitment were more likely to express an intent to remain in those positions on a short- and long-term basis.